A case study of implementing a renovation concept - Matthias Haase (Acta Polytechnica CTU Proceedings)
There is an untapped potential for reducing GHG emissions by district renovation. It needs a detailed Energy Master Planning (EMP) of the district and support for the decision-making processes. If applied in a comprehensive manner it can contribute significantly to reducing energy consumption and thus to a long-term sustainable development of districts and climate neutrality in our cities.The EMP typically includes combinations of energy supply and consumption, but it is equally important to understand the different solutions for district renovation. The multi-owner structure in many districts requires another set of solution finding that is embedded in potential analysis, stakeholder analysis, participative planning, and multi-actor-Management. A district near Winterthur, Switzerland was used as a case study. Site visits and structured interviews with key stakeholders were used to collect data which was then used to model the technical-economic situation and to determine the possibilities for the future.